2010
DOI: 10.1002/anie.200907289
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Doped Ordered Mesoporous Graphitic Arrays with High Electrocatalytic Activity for Oxygen Reduction

Abstract: These materials are no dopes: Nitrogen‐doped ordered mesoporous graphitic arrays (NOMGAs) prepared by a metal‐free procedure exhibited higher electrocatalytic activity than the commercially available Pt–C catalyst (see plot), excellent long‐term stability, and resistance to crossover effects in the oxygen‐reduction reaction (ORR). Graphite‐like nitrogen atoms appear to be responsible for the excellent electrochemical performance in the ORR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
815
3
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,274 publications
(860 citation statements)
references
References 36 publications
32
815
3
10
Order By: Relevance
“…Generally, they have been synthesized with the help of metal catalysts (e.g Co or Fe), which had raised the concern that the ORR activity was attributable to the metal-nitrogen complexes as in the well-known case of metal-porphyrins [9]. However, synthesis methods that do not use any metal precursors or catalysts have been recently developed and ORR activity of the catalyst has been preserved [15,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, they have been synthesized with the help of metal catalysts (e.g Co or Fe), which had raised the concern that the ORR activity was attributable to the metal-nitrogen complexes as in the well-known case of metal-porphyrins [9]. However, synthesis methods that do not use any metal precursors or catalysts have been recently developed and ORR activity of the catalyst has been preserved [15,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…graphene [10,[23][24][25][26][27][28][29][30][31][32][33], carbon nanotubes [11,20,21,[34][35][36][37][38][39][40][41][42][43], carbon nanofibers [12,[44][45][46][47], mesoporous carbon [15,22], graphitic carbon [48,49], carbon spheres [19,[50][51][52][53], carbon nanocages 4 [54], flower-like carbon [55], carbon aerogel [56,57], vesicular carbon [58], nanodiamonds [59]) relatively few have been tested in actual fuel cell conditions [58,[60][61][62]…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] In order to decrease the cost of electrocatalysts and eliminate their dependence on noble metals, various non-noble metal catalysts have been explored recently as alternatives to the Pt-based electrocatalysts, which include chalcogenide catalysts, [15][16][17][18][19] transition metal macrocyclic compounds, [20][21][22] transition metallic oxides [23][24][25][26][27] and carbon-based catalysts. [28][29][30][31][32][33][34][35] In particular, carbon-based catalysts doped with the heteroatoms such as nitrogen (N) or boron (B) have been paid much attention and been proposed as typical non-noble metal catalysts for ORR [36][37][38] in alkaline media. Especially, since Gong et al 37 reported the superior activity and stability of nitrogen doped carbon nanotube in alkaline solution, the heteroatom doped carbon materials have been expected to be promising alternative Pt-based catalysts.…”
mentioning
confidence: 99%
“…Moreover, addition of nitrogen varies the charge distribution of the carbon network so that the C atoms adjacent to N become more positively charged, resulting in an enhanced interaction with the adsorbing molecule and thus lower activation barrier for its decomposition [96]. 41 Recently, a variety of metal-free nitrogen doped CNMs have been synthesized in the form of CNTs [97][98][99][100][101][102], CNFs [103,104], graphene [105,106], mesoporous carbon [107], carbon nanocages [108], carbon spheres, hollow carbon nanoparticles [109], etc. In this thesis the synthesis and electrocatalytic activity of N-FWCNTs and N-GNPs for the ORR have been investigated.…”
Section: Cnms As Pt-free Catalystsmentioning
confidence: 99%